Livestock Information System Using Android Smartphone - Mohd Hisyam, Mohd Ariff; Ismarani, Ismail (IEEE, 2013)
These days livestock farming can contributes to the huge profit income to the farmers. The main element must be considered in order to ensure the animal is in good condition is by monitoring the health status. The health data collections in the field such as core body temperature, heart rate, medications, call for fast and accurated method, which allows repeated measurement through time. One of the popular technique for measuring the spatial distribution and temporal variation of livestock health data content is by using Android Smartphone. In this paper we present the development project called Livestock Information System (LIS) on Android Smartphone to access continuously the animal state of health data. This project use Android operating system where equipped with Bluetooth technology where it will communicate and process the wearable health sensors reading and display the exact temperature and heart rate of the livestock. In order to gather statistical data from mobile based to PC via Web services, Google Cloud Storage enable this interaction. This device is reliable and accurate in determining the livestock health status.